An Assessment of Resource Suitability and Visitor Perceptions in The Bahowo Mangrove Ecotourism Area - Tommy M. Kontu; Dannie R. S. Oroh; Meidy Wollah; Oktavianus Lintong (Sam Ratulangi University, 2025)
Mangrove ecotourism is a strategic approach to coastal area management that integrates environmental conservation and community empowerment. This study aims to assess the resource suitability level and evaluate visitor perceptions in the Bahowo mangrove ecotourism area, Manado City. Primary data were collected through field surveys using the Tourism Suitability Index (IKW) and perception questionnaires based on a Likert scale. Five ecological parameters were analysed to obtain the IKW score, while six visitor perception aspects were evaluated to assess satisfaction and revisit intention. The results revealed an IKW score of 1.84, classified as